Sugarcane Ratoon Stunting - Philippe Rott; Sushma Sood; Jack C. Comstock; Robert A. Gilbert; Hardev S. Sandhu (EDIS, 2018)
Ratoon stunting is a major disease of sugarcane that can cause significant yield losses. It is caused by the bacterium Leifsonia xyli subsp. xyli. This pathogen is mainly spread by infected stalk cuttings and contaminated harvesting knives. Ratoon stunting is controlled by planting disease-free stalk cuttings and resistant sugarcane cultivars. This 3-page fact sheet is a minor revision written by P. Rott, S. Sood, J. C. Comstock, R. A. Gilbert, and H. S. Sandhu, and published by the Agronomy Department, March 2018.